Penilaian Kematangan Manajemen Data Master, Studi Kasus Rumah Terapi XYZ - Asymala, Asymala Permata Sari; Hidayanto, Achmad Nizar (Universitas Samudra, 2024)
Master Data Management (MDM) provides a way for an organization to ensure its data consolidation and integration across the whole system using a single master data set, thus benefiting with seamless operational and analytical processes. Not all organizations have good directions nor know the strategies of master data management. Master Data Maturity Management Model (MD3M) provides a blueprint for organizations to assess their currently implemented master data maturity management. The case study in this paper assessed MDM implementation in Therapy House XYZ by using MD3M by Spruitz and Pietzka. The referred MD3M has 5 key topics and 13 focus areas regarding master data management implementations. By assessing each of these points, organizations could know in which directions or area they could improve regarding MDM. The data were collected by using questionnaires and interviewing a Subject Matter Expert (SME) that handled the data management and system in the organization. This research found that 57% or 36 out of 63 of MD3M capabilities have been implemented. The missing capabilities are spread thorough the 5 key topics. The organization can achieve a higher maturity level by implementing the missing capabilities. Keywords: Master Data, Master Data Management, Master Data Maturity Assessment, MD3M